The Arctic Council Inclusive of Non-Arctic Perspectives: seeking a new balance - Graczyk, Piotr (2012)
The Arctic Council’s (AC) openness to the outside world has become an increasingly important issue in the current debate on its shape and place in the Arctic governance structure. The growing interest of states such as China and entities like the European Union in obtaining Observer status on the Council, and the search for an enhanced role by existing Observers, has triggered an emotional debate between the Arctic states, Observers and Permanent Participants. Admission of new non-Arctic actors as Observers and strengthening the role of the status might have broader consequences for the Council’s design, functioning and general direction in which international relations in the Arctic would unfold. This article attempts to develop a new concept of the place and form of the Arctic Council from the perspective of a redefined non-Arctic participation. It seeks the most appropriate way of involvement of non-regional players into the Arctic Council’s activities that would be congruent with all parties’ interests and would not encroach upon the unique character of the Council. To achieve this goal, a three-step approach is employed. First, earlier concepts about the improvement of the Arctic Council are briefly reviewed and summarised. Second, the stances and policies of the Arctic states on the reform of the AC are explored. Third, the current political context in reference to the Observer debate is described. The new concept is introduced within the framework set by conclusions emerging from these three backgrounds.